2021
DOI: 10.1111/jpn.13591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protease supplementation on growth performance, water quality, blood parameters and intestinal morphology of Nile tilapia (Oreochromisniloticus)

Abstract: This study was conducted to evaluate the effect of using protease in diets of Nile tilapia on growth performance, water quality, blood parameters and intestinal morphology. The cost of these diets and their return on fish performance was calculated. A total of 360 fish were randomly allocated into four groups with triplicates (30 fish per replicate). Four diets were formulated; two controls (without protease supplementation) and two experimental diets (supplemented with protease). The first control diet contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
(59 reference statements)
3
14
0
Order By: Relevance
“…In current study, total protein and albumin remained unaffected by protease supplementation. Similar to our results, no significant differences in glucose, albumin and total protein content were reported for protease supplementation in gibel carp (Liu et al, 2018) and tilapia (Saleh et al, 2021). These findings confirmed that optimum protease supplementation did not induce stress on fish physiology.…”
Section: Biochemical Parameterssupporting
confidence: 91%
See 4 more Smart Citations
“…In current study, total protein and albumin remained unaffected by protease supplementation. Similar to our results, no significant differences in glucose, albumin and total protein content were reported for protease supplementation in gibel carp (Liu et al, 2018) and tilapia (Saleh et al, 2021). These findings confirmed that optimum protease supplementation did not induce stress on fish physiology.…”
Section: Biochemical Parameterssupporting
confidence: 91%
“…Similarly, Hassan et al (2019) reported that dietary protease supplementation improved RBCs count in tilapia. Contrarily, no significant difference in RBCs count and Hb level was observed in tilapia and gibel carp in response to protease supplemented diets (Saleh et al, 2021; Liu et al, 2018). Besides this, no significant difference in WBCs was observed among all treatments in this study.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations